An Effective Flocculation Method to the Kaolin Wastewater Treatment by a Cationic Polyacrylamide (CPAM): Preparation, Characterization, and Flocculation Performance - Badradine Zakaria Djibrine; Huaili Zheng; Moxi Wang; Shuang Liu; Xiaomin Tang; Sarfaraz Khan; Andrea Navarro Jimenéz; Li Feng (International Journal of Polymer Science)
P(AM-DMC) (PAD) was synthesized by ultraviolet- (UV-) initiated copolymerization with methacryloxyethyl trimethyl ammonium chloride (DMC) and acrylamide (AM) as the monomers and initiator 2,2-azobis [2-(2-imidazolin-2-yl) propane] dihydrochloride (VA-044) as the photoinitiator. Parameters that affect the molecular weight were reviewed by using the single-factor approach. The results showed that the molecular weight (MW) of PAD could come to 7.88 × 106 Da with the optimum polymerization conditions as follows: monomer concentration of 30%, monomer mass ratio m(AM) : m(DMC) of 3 : 1, initiator concentration of 0.6‰, illumination time of 80 min, solution pH value of 4.5, and incident light intensity of 1000 μW cm−2. The PAD was represented by several instruments. The results of FTIR and 1H NMR showed that PAD was indeed polymerized by AM and DMC. The results of TGA showed that PAD was very stable at room temperature while the result of SEM revealed that PAD had a porous structure and rough surface. For PAD used as flocculant in kaolin wastewater treatment, the results confirmed that, at optimal conditions, the turbidity and the floc size d50 could reach to 5.9 NTU and 565.936 μm, respectively, at the optimal conditions (pH = 7.0 and dosage = 2 mg l−1). Kaolin wastewater flocculation test outcome reveals that the PAD with high cationic degree and intrinsic viscosity could boost the charge neutralization and bridging capability. Consequently, the result is an excellent flocculation performance of treating kaolin wastewater.